Pengaruh Corporate Governance Terhadap Kinerja Perusahaan(Studi Kasus pada Perusahaan Perbankan Go Public yang Terdaftar di Bursa Efek IndonesiaTahun 2011-2015) - Wati, Erna Kurnia; , Dr. Syamsudin, MM (2017)
This research aims to find out the effect of managerial ownership, institutional ownership, and public ownership toward company performance. In this research, company performance proxies with Return on Assets (ROA). The collecting data is using purposive sampling method toward the company. The banking of Go Public registered in Indonesia Stock Enhance in 2011-2015. The technique of analyzing data in this research is using linear multiple linear regression analysis, purposive sampling method of the 41 population of banking company. There are 20 banking companies used as samples. The number of research observation is 100 observations. This research finds the positive and significance between managerial ownership and public ownership toward the company performance while institutional ownership in significance has negative effect. The result supports the agency theory shows that managerial ownership gives effective supervision from the outside then increase profitability and reduce the possibility of opportunistic behave by management and increase the performance in the end. Whereas, institutional ownership is not affecting the company performance.